Love rules : silent Hollywood and the rise of the managerial class - Cooper, Mark Garrett (University of Minnesota Press, 2003)
Through close study of such films as Birth of a Nation, Enoch Arden, The Crowd, Why Change Your Wife? and The Jazz Singer, Mark Garrett Cooper uncovers an intimate connection between Hollywood romances of the silent era and the empowerment of a managerial class.